Proximal aortic diameter evolution in hypertensive patients with mild-to-moderate aortic dilatation: a 5-year follow-up experience. Issue 4 (April 2020) - Leone, Dario; Cina, Andrea; Tosello, Francesco; Sabia, Luca; Vallelonga, Fabrizio; Avenatti, Eleonora; Astarita, Anna; Mingrone, Giulia; Veglio, Franco; Ridolfi, Luca; Milan, Alberto
Abstract : Background: Aortic dilatation is common in hypertensive patients and is associated with higher risk of cardiovascular events. Parameters predicting further dilatation during lifetime are poorly understood. Aim: To predict the midterm aortic diameter evolution in a cohort of hypertensive patients with known aortic dilatation at Sinus of Valsalva (SOV) level. Methods: We prospectively analyzed a cohort of essential hypertensive outpatients without any other known risk factor for aortic dilatation. They underwent serial echocardiographic evaluations from 2003 to 2016. Results: Two hundred and forty-two hypertensive outpatients with a mild-to-moderate (37–53 mm) aortic dilatation were followed up for at least 5 years. Mean growth rate was 0.08 ± 0.35 mm/year. No clinical or anthropometric parameters were significantly different in patients with and without aortic diameter increase. Aortic z score (number of standard deviations from the average value observed in the general population) at baseline was inversely associated with growth rate ( R 2 0.04, P  < 0.05). Aortic diameter at first visit, demographic and echocardiographic variables were major determinants of aortic diameter at second visit, accounting for about 90% of its total variability. Conclusion: Mean growth rate of proximal aorta in hypertensive patients with known aortic dilatation was of about 0.1 mm/year. Dilatation over time is slower in patients with increased rather than normal aortic z score. Eventually, it could be possible to reliably predict aortic diameter at few months from first visit. Abstract : Supplemental Digital Content is available in the text